Analisis ketimpangan pembangunan wilayah antar provinsi di Pulau Sumatera - Muhammad Ridho; Zulgani Zulgani; Erni Achmad (e-Jurnal Perspektif Ekonomi dan Pembangunan Daerah, 2022)
Regional development inequality is a strategic issue that is currently being discussed. Sumatra Island has the highest development value when compared to other islands in Indonesia, so this purpose is to measure and analyze development assessments between provinces on Sumatra Island. As well as the influence of government participation, support, investment, labor and GRDP on regional development between provinces on the island of Sumatra. The research method used in this research is descriptive- quantitative analysis method. The value of regional development between provinces on the island of Sumatra from 2010 - 2019 has decreased every year. The results of panel data regression analysis using the Fixed Effect Model (FEM) approach, the results show that the variables of government expenditure, investment and labor have a negative and significant effect on KPW. While the GRDP variable has a positive and significant effect on KPW.